A novel biallelic nonsense variant in SLC38A3 causing epileptic encephalopathy in an Indian family. Issue 5 (20th December 2022) - Alawbathani, Salem; Khan, Suliman; Westenberger, Ana; Beetz, Christian; Lingappa, Lokesh
Abstract :